Comparative genomic analysis of Staphylococcus lugdunensis shows a closed pan-genome and multiple barriers to horizontal gene transfer - Xavier Argemi; Dorota Matelska; Krzysztof Ginalski; Philippe Riegel; Yves Hansmann; Jochen Bloom; Martine Pestel-Caron; Sandrine Dahyot; Jérémie Lebeurre; Gilles Prévost (BMC Genomics, 2018)
Abstract Background Coagulase negative staphylococci (CoNS) are commensal bacteria on human skin. Staphylococcus lugdunensis is a unique CoNS which produces various virulence factors and may, like S. aureus, cause severe infections, particularly in hospital settings. Unlike other staphylococci, it remains highly susceptible to antimicrobials, and genome-based phylogenetic studies have evidenced a highly conserved genome that distinguishes it from all other staphylococci. Results We demonstrate that S. lugdunensis possesses a closed pan-genome with a very limited number of new genes, in contrast to other staphylococci that have an open pan-genome. Whole-genome nucleotide and amino acid identity levels are also higher than in other staphylococci. We identified numerous genetic barriers to horizontal gene transfer that might explain this result. The S. lugdunensis genome has multiple operons encoding for restriction-modification, CRISPR/Cas and toxin/antitoxin systems. We also identified a new PIN-like domain-associated protein that might belong to a larger operon, comprising a metalloprotease, that could function as a new toxin/antitoxin or detoxification system. Conclusion We show that S. lugdunensis has a unique genome profile within staphylococci, with a closed pan-genome and several systems to prevent horizontal gene transfer. Its virulence in clinical settings does not rely on its ability to acquire and exchange antibiotic resistance genes or other virulence factors as shown for other staphylococci.